Language as a resource for ethnic and cultural identity: experience of Latvian expats in Sweden - Maruta Pranka; Ilze Koroļeva; Ginta Elksne (Revista Română pentru Studii Baltice şi Nordice, 2021)
The aim of this article is to investigate the experience and significance of the use and preservation of Latvian for native language maintenance, national culture and identity in the Nordic countries. This has been done by analysing native (heritage) language as a resource for ethnic and culture identity. The aim of the article is to ascertain the language situation in the diaspora, explore practices and perspectives regarding the sustaining of Latvian language and ethnic culture. From the theoretical point of view, the data is approached with reference to P. Bourdieu`s view on language skills as linguistic capital, a form of culture capital. The paper uses a combination of both quantitative survey and in-depth interviews with Latvian emigrants, especially those in the Nordic countries.